Large-scale metabarcoding analysis of epipelagic and mesopelagic copepods in the Pacific - Hirai, Junya (PLoS One, 2020)
A clear insight into the large-scale community structure of planktonic copepods is critical to understanding the mechanisms controlling diversity and biogeography of marine taxa in terms of their high abundance, ubiquity, and sensitivity to environmental changes. Here, we applied a 28S metabarcoding approach to large-scale communities of epipelagic and mesopelagic copepods at 70 stations across the Pacific Ocean and three stations in the Arctic Ocean. Major patterns of community structure and diversity, influenced by water mass structures, agreed with results from previous morphology-based studies. However, a large-scale metabarcoding approach could detect community changes even under stable environmental conditions, including changes in the north/south subtropical gyres and east/west areas within each subtropical gyre. There were strong effects of the epipelagic environment on mesopelagic communities, and community subdivisions were observed in the environmentally stable mesopelagic layer. In each sampling station, higher operational taxonomic unit (OTU) numbers and lower phylogenetic diversity were observed in the mesopelagic layer than in the epipelagic layer, indicating a recent rapid increase in species numbers in the mesopelagic layer. The phylogenetic analysis utilizing representative sequences of OTUs revealed trends of recent emergence of cold-water OTUs, which are mainly distributed at high latitudes with low water temperatures. Conversely, the high diversity of copepods at low latitudes was suggested to have been formed through long evolution under high water temperature conditions. The metabarcoding results suggest that evolutionary processes have strong impacts on current patterns of copepod diversity, and support the “out of the tropics” theory explaining latitudinal diversity gradients of copepods. Diversity patterns in both epipelagic and mesopelagic copepods was highly correlated to sea surface temperature; thus, predicted global warming may have a significant impact on copepod diversity in both layers.